2020
DOI: 10.1186/s12893-020-00936-z
|View full text |Cite
|
Sign up to set email alerts
|

Isoperistaltic versus antiperistaltic uncut Roux-en-Y anastomosis after distal gastrectomy for gastric cancer: a propensity score matched analysis

Abstract: Background The uncut Roux-en-y anastomosis (URYA) has some clinical advantages after distal gastrectomy (DG). Little evidence exists regarding the influence of peristalsis on this anastomosis. We aimed to evaluate short-term outcomes of isoperistaltic URYA (iso-URYA) comparing with antiperistaltic URYA (anti-URYA) after DG. Method Patients who underwent URYA for gastric cancer (GC) between January 2016 and December 2018 were selected from Shanghai Changhai Hospital, Navy Medical University. Short-term outcom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…According to a previous study, closing the afferent loop jejunum may not result in permanent healing between the mucosa and the mucosa, which is the main reason for the recanalization of the bowel. [29][30][31] This finding indicates that the linear stapler is not complete enough to close the afferent limb jejunum and needs to be further improved. Some scholars have proposed different methods of closing the afferent loop, and it has been reported that ligation with a 7-gauge silk thread can effectively reduce the recanalization rate.…”
Section: Discussionmentioning
confidence: 98%
“…According to a previous study, closing the afferent loop jejunum may not result in permanent healing between the mucosa and the mucosa, which is the main reason for the recanalization of the bowel. [29][30][31] This finding indicates that the linear stapler is not complete enough to close the afferent limb jejunum and needs to be further improved. Some scholars have proposed different methods of closing the afferent loop, and it has been reported that ligation with a 7-gauge silk thread can effectively reduce the recanalization rate.…”
Section: Discussionmentioning
confidence: 98%